'I am Trying to Believe': Dystopia as Utopia in the Year Zero Alternate Reality Game - Hall, Alexander Charles Oliver (Eludamos: Journal for Computer Game Culture, 2009)
A major symptom of postmodernity is the loss of utopian energy, of which the popularity of dystopian cultural production is evident. The dystopian genre, however, is cautionary, and thus utopian. Associated is the influence of technology on post-utopian culture—although it has been viewed pessimistically, technology allows for new ways of telling dystopian stories. One such mode of telling dystopian stories is the Alternate Reality Game (ARG), a narrative, multi-media game, using several different technologies that puts the player in a fictional reality. One ARG that exemplifies the idea of dystopia as having utopian energy is Nine Inch Nails’ Year Zero, which shows that technology can have utopian energy, offering new ways of telling dystopian stories such as via the ARG, thus locating some utopian energy in postmodern culture through the form’s culturally critical structure and interactive nature, which equals a call to action against the dystopian nature of contemporary society.